SPE Annual Technical Conference and Exhibition 2012
DOI: 10.2118/160918-stu
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Formation Damage Reduction: Mud Cake Removal and Mud Filtration Treatment using Ultrasonic Wave Radiation

Abstract: Interactions of reservoir with drilling and completion fluids, mud cake and mud filtration, lead to formation permeability damages which result in reduction of production rate. For increasing the production rate and treating the formation damage, normally Matrix Acidizing and Hydraulic Fracturing treatment are used. Although hydraulic fracturing and matrix acidizing are effective operations, they have some critical issues. For instance, they need some specialized fluids that require the petroleum industry to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Ultrasound has also been used together with other techniques to fight formation damage caused by drilling and completion fluids [34], pore blockage by mud cake and mud particles [35] and fines [36], and partially hydrolyzed Polyacrylamide (PHPAM)-induced formation damage [37]. Overall, it was found that ultrasound enhanced the applied techniques and improved pore permeability [34], [36], [37].…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediamentioning
confidence: 99%
“…Ultrasound has also been used together with other techniques to fight formation damage caused by drilling and completion fluids [34], pore blockage by mud cake and mud particles [35] and fines [36], and partially hydrolyzed Polyacrylamide (PHPAM)-induced formation damage [37]. Overall, it was found that ultrasound enhanced the applied techniques and improved pore permeability [34], [36], [37].…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediamentioning
confidence: 99%